1999
DOI: 10.1038/sj.ki.4491164
|View full text |Cite
|
Sign up to set email alerts
|

Predicting renal survival in primary focal glomerulosclerosis from the time of presentation

Abstract: For a patient with primary FGS, these models can be used to predict the risk of developing chronic renal failure at any time and the median renal survival, given the proportion of tubulointerstitial fibrosis and plasma creatinine at the time of presentation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
15
0

Year Published

2006
2006
2015
2015

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 34 publications
(17 citation statements)
references
References 2 publications
0
15
0
Order By: Relevance
“…Only the extent of interstitial fibrosis has been shown to consistently predict a poor prognosis [32,40]. In our pediatric population we found only the proportion of glomeruli with global sclerosis to be a continuous variable predictive of CKD.…”
Section: Discussionmentioning
confidence: 93%
See 4 more Smart Citations
“…Only the extent of interstitial fibrosis has been shown to consistently predict a poor prognosis [32,40]. In our pediatric population we found only the proportion of glomeruli with global sclerosis to be a continuous variable predictive of CKD.…”
Section: Discussionmentioning
confidence: 93%
“…The presence of nephrotic-range proteinuria has been associated with a poor prognosis in primary FSGS, with 50% of patients reaching CKD over 6 to 8 years [10,31,37,41]. However, a recent study applying multivariate analysis did not demonstrate the degree of proteinuria as an independent predictor of renal survival [32]. Yoshikawa et al [28] have demonstrated a similar prognosis in pediatric patients with FSGS with and without nephrotic syndrome.…”
Section: Discussionmentioning
confidence: 94%
See 3 more Smart Citations